Evaluating quality of health services in health centres of Zanjan district of Iran - Ali Mohammadi; Jamshid Mohammadi (Wolters Kluwer Medknow Publications, 2012)
To assess quality of health services in Zanjan health centres based on clients' expectations and perceptions. The study was conducted by using service quality (SERVQUAL) scale on a sample of 300 females, clients of health care centres in the district of Zanjan, selected by cluster sampling. The results indicated that there were negative quality gaps at five SERVQUAL dimensions. The most and least negative quality gap mean scores were in reliability dimension (-2.1) and tangible (-1.13) respectively. There was statistically significant difference between clients' perceptions and expectations mean scores at all of the five service quality dimensions (P<0.001). The negative quality gap level in health service dimensions can be used as a guideline for redistribution of resources and managerial attempts to reduce quality gaps and improvement of health care quality.